A Station in Motion: Termini as Heterotopia. (2nd October 2017) - Brioni, Simone
Abstract: Drawing on Michel Foucault's definition of heterotopia, the article analyses the filmic and literary representation of Stazione Termini, Rome's main train station. The Fascist architectural project, which mirrors an idea of the nation as homogeneous, monolithic, and white, begins to be challenged in the post-World War II representations of Termini which depict the station as the place where liminal and unexpected experiences can occur and accepted moral codes of behaviour are put into question. The article then focuses on the recent representation of Termini as a key place of contact with and among immigrants. While migration literature describes the station as a place of belonging, other contemporary representations of Termini depict it as a non-place, revealing the fear of a globalised world. The representation of Termini either as an isolated place in the urban geography of Rome or as a place that mirrors the multicultural reality of present-day Italy highlights a tension between different ways of practicing the same space.